Fine particle pH during severe haze episodes in northern China. Issue 10 (21st May 2017) - Liu, Mingxu; Song, Yu; Zhou, Tian; Xu, Zhenying; Yan, Caiqing; Zheng, Mei; Wu, Zhijun; Hu, Min; Wu, Yusheng; Zhu, Tong
Abstract: Aerosol acidity plays an important role in atmospheric chemistry. China emits large amounts of SO2, NO x, and NH3 into the atmosphere, but aerosol acidity is poorly characterized. In this study, simultaneous 1 h measurements of particulate and gaseous compositions along with the ISORROPIA‐II thermodynamic equilibrium model were used to study aerosol acidity during severe haze episodes in northern China. The summed concentration of sulfate, nitrate, and ammonium was 135 ± 51 μg/m 3 with a maximum of 250 μg/m 3, and the gas‐phase NH3 mixing ratio was 22 ± 9 ppb. Fine particles were moderately acidic, with a pH range of 3.0–4.9 and an average of 4.2, which was higher than those in the United States and Europe. Excess NH3 and high aerosol water content are responsible for the relatively lower aerosol acidity. These results suggest that the new pathways for sulfate production in China proposed by recent studies should be revisited. Key Points: Aerosol acidity plays an important role in atmospheric chemistry but poorly characterized in northern China with significant gaseous emissions Fine particles were moderately acidic during severe haze episodes in northern China, with its pH ranging from 3.0 to 4.9 and on average 4.2 Excess ammonia and abundant aerosol water content lead to relatively lower aerosol acidity in northern China compared to those in United States and Europe